MANAJEMEN APLIKASI SISTEM ZONASI DALAM PENERIMAAN PESERTA DIDIK BARU (PPDB) TINGKAT SEKOLAH MENENGAH PERTAMA (SMP): (Studi Kasus: DISDIK Kabupaten Indramayu) - Mufid Mukhfid (Jurnal Investasi, 2020)
In order to carry out the mandate of the Ministry of Education and Culture (Kemendikbud). And in 2019 the Ministry of Education and Culture implemented a system called the Zoning System which regulates student admission in a zone that will be applied to all regions in Indonesia which are set according to Minister of Education and Culture Regulation No. 51 of 2018[1]. Currently in the New Student Admissions Process (PPDB) in its application is still manual and uses an offline system that is divided in every school so that its implementation is still experiencing problems, where it is difficult to get valid location data for distance determination, lack of transparency of information, less effective, even many schools do not follow the rules in accordance with existing regulations. Methodology in the Development of "Application of Zoning System in Accepting New Students (PPDB) for Junior High School (JHS) in Inddikayu Regency Disdik" with a structured approach [2] and the tools used are Data Flow Diagrams (DFD)[3], Entity Relation Ship Diagram (ER-D)[4], and Relationship Table. It is expected that the results of the developed application provide solutions to existing problems and can produce fast and accurate information for policymakers. Dalam rangka menjalankan amanat Kementrian Pendidikan dan Kebudayaan (Kemendikbud). Dan pada tahun 2019 Kemendikbud melakukan penerapan sistem yang disebut dengan Sistem Zonasi yang dimana mengatur penerimaan peserta didik pada suatu zona yang akan diterapkan untuk seluruh wilayah di Indonesia yang di atur sesuai pada Permendikbud Nomor 51 Tahun 2018[1] Saat ini dalam proses Penerimaan Peserta Didik Baru (PPDB) pada penerapannya yang masih manual dan menggunakan sistem yang bersifat offline yang terbagi pada setiap sekolah sehingga pelaksanaannya masih mengalami masalah, yang dimana sulitnya mendapatkan data lokasi yang valid untuk penentuan jarak, kurangnya transparansi informasi, kurang efektif, bahkan banyak sekolah yang tidak mengikuti peraturan sesuai dengan peraturan yang ada. Metodologi dalam Pengembangan “Aplikasi Sistem Zonasi Dalam Penerimaan Peserta Didik Baru (PPDB) Tingkat Sekolah Menengah Pertama (SMP) Di Disdik Kabupaten Indramayu” ini dengen pendekatan Terstruktur [2] dan Tools yang digunakan adalah Data Flow Diagram (DFD) [3], Entity Relation Ship Diagram (ER-D) [4], dan Relasi Tabel. Diharapkan hasil dari aplikasi yang dikembangkan memberikan solusi permasalahan-permasalahan yang ada dan dapat menghasilkan informasi yang cepat dan tepat bagi pemangku kebijakan